Profane-sacred Attributes in The Designof Funeral Services in Yogyakarta and Solo, Indonesia - Mustika Wardhani (Journal of Architectural Design and Urbanism, 2022)
Funeral services are part of public facilities with deep meaning for the mourners to ‘say goodbye’. In Indonesia, funeral services are regulated in Spatial and Regional Planning that adapts to the local context and culture. However, the development of funeral services encountered various obstacles in the availability of adequate facilities and have ‘less-meaning’ in small towns. The death of a loved one causes psychological distress for the family and those left behind. This problem underlies study related to the meaning of profane-sacred values in funeral services. The method used is a qualitative study with a storytelling approach through observations at funeral homes and crematoriums in Yogyakarta and Solo, Indonesia. This study shows that the profane zones of funeral services can manifest in flexibility, continuity of space, relief of spatial dimensions, and clarity of circulation. The 'chaotic' phases of mourning can be neutralised with monochrome colours to create an atmosphere of consolation. Meanwhile, sacred zones can be applied rigid, angular, and centred as a form of honour. Landscape interventions may aim to neutralise a grief situation and potentially be an aspect of natural healing. Moreover, landscape planning around the main building can address sustainability and environmental balance. The results of this study are expected to provide a discourse that funeral buildings are not only seen as 'a space of activity', but beyond that, it has a significant role in healing aspects in bereavement conditions.